2021
DOI: 10.1021/acs.macromol.1c00554
|View full text |Cite
|
Sign up to set email alerts
|

Intercalation and Ordering of F6TCNNQ and F4TCNQ Dopants in Regioregular Poly(3-hexylthiophene) Crystals: Impact on Anisotropic Thermoelectric Properties of Oriented Thin Films

Abstract: Redox doping is widely used to transform polymer semiconductors such as regioregular poly(3-hexylthiophene) into conducting polymers. Strong acceptor molecules such as F 6 TCNNQ and F 4 TCNQ have been used for sequential doping of aligned P3HT films to produce films with enhanced thermoelectric properties along the chain direction. This study uses Polarized UV-vis-NIR spectroscopy and electron diffraction to clarify the way dopant molecules are introduced in the crystals of P3HT. A structural model is obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
64
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 37 publications
(73 citation statements)
references
References 39 publications
8
64
1
Order By: Relevance
“…The recent structural refinement for F 6 TCNNQ-doped P3HT has shown that doping P3HT with F 6 TCNNQ induces a shift of P3HT backbones so as to group alkyl side chains and create cavities to host the dopant molecules in the crystal. [19] The present results demonstrate that doping with MB does not induce such a structural reorganization within π -stacks. There is thus evidence that MB is only marginally intercalated inside the P3HT lattice.…”
Section: Impact Of Doping On the Structure Of Oriented P3ht Probed By...mentioning
confidence: 49%
See 4 more Smart Citations
“…The recent structural refinement for F 6 TCNNQ-doped P3HT has shown that doping P3HT with F 6 TCNNQ induces a shift of P3HT backbones so as to group alkyl side chains and create cavities to host the dopant molecules in the crystal. [19] The present results demonstrate that doping with MB does not induce such a structural reorganization within π -stacks. There is thus evidence that MB is only marginally intercalated inside the P3HT lattice.…”
Section: Impact Of Doping On the Structure Of Oriented P3ht Probed By...mentioning
confidence: 49%
“…The incremental concentration doping (ICD) of P3HT films leads to an improvement of TE properties based on a progressive intercalation of dopants in the pristine polymer structure as compared to direct doping using dopant solutions of high concentration. [18,19,30] The same oriented film was thus dipped in solutions of MB/ACN of increasing concentration [MB] and the anisotropic conductivity and Seebeck coefficient were measured along (//) and normal (⊥) to the rubbing direction (chain direction) (see Figure 1b-d).…”
Section: Anisotropic Thermoelectric Propertiesmentioning
confidence: 99%
See 3 more Smart Citations